Paciente en embarazo gemelar de 33 años de edad con diabetes. - Peñafiel Vinces, Jorly Bryan (2021)
Gestational diabetes is defined as any intolerance to carbohydrates, which is first diagnosed during the gestation period. Pregnant women diagnosed with gestational diabetes predispose a much higher risk of morbidity and mortality during pregnancy, childbirth and postpartum. In the present clinical case, the data of a 33-year-old patient who is in a state of twin gestation, who is diagnosed with gestational diabetes at week 27, are detailed, so she is referred to the nutrition department as part of the prophylactic measures to avoid maternal fetal complications. The evaluation of the nutritional status is carried out through the anthropometric, biochemical, clinical and dietary assessment, by means of which the patient was diagnosed with an excessive intake of carbohydrates evidenced in her biochemical values of fasting glycemia and by the reminder of 24 hours. With this, a hypercaloric diet is prescribed due to its twin and hyperprotein gestational state, normoglycidic and normogram, the intake of dietary fiber was also increased. After one month of nutritional treatment, nutritional follow-up is carried out at 31 weeks of gestation and very good results are reported, fasting glycemia values were normalized and no complications associated with gestational diabetes are reported.